ANALYSIS OF THE URGENCY OF FORMATION OF SPECIAL AUTONOMOUS REGION OF SOUTH PAPUA PROVINCE - Irwan Abdu Nugraha; Ahmad Baihaqi Midhol (Adisam Publisher, 2025)
A series of policies have been implemented in Papua, but many parties consider them still not optimal. So there was a demand for the formation of a new autonomous region in the Ha Anim traditional territory which is part of Papua Province to become the new Province of South Papua. Seeing this phenomenon, this research focuses on; What is the background to the emergence of the demand for the formation of an autonomous region for South Papua and what is the urgency of policy making? This research method uses a type of library research to examine various references with the subject of discussing the formation of special autonomy for the Province of South Papua. The research results explain the existence of three dimensions in the background to the demand for the formation of a special autonomous region for South Papua Province, namely; political, technical dimensions and regional disparities. This research also explains the urgency factors for the policy of establishing a special autonomous region for South Papua Province, including; human resource factors, regional financial factors, infrastructure factors and organizational and managerial factors.